2012
DOI: 10.3174/ajnr.a3259
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Aphasia Outcome Using Diffusion Tensor Tractography for Arcuate Fasciculus in Stroke

Abstract: BACKGROUND AND PURPOSE:The AF is an important neural tract in language function. We investigated aphasia outcome according to DTT findings for AF in the early stage of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 43 publications
(57 reference statements)
2
79
2
1
Order By: Relevance
“…19 All these patterns of tumors cause DTI parameter changes, in particular FA decrease, in involved regions. 20 Furthermore, the presence of voxels with FA values lower than the DTI threshold (commonly set to 0.2) causes an interruption of reconstructed WM tracts, 21 and the use of an FA threshold lower than 0.2 results in poor accuracy of major eigenvector-direction estimation. 1 These limitations can produce 3 negative effects on tractographic presurgical planning, particularly in CST evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 All these patterns of tumors cause DTI parameter changes, in particular FA decrease, in involved regions. 20 Furthermore, the presence of voxels with FA values lower than the DTI threshold (commonly set to 0.2) causes an interruption of reconstructed WM tracts, 21 and the use of an FA threshold lower than 0.2 results in poor accuracy of major eigenvector-direction estimation. 1 These limitations can produce 3 negative effects on tractographic presurgical planning, particularly in CST evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 This WM bundle connects to Broca, Wernicke, and Geschwind areas and other brain regions involved in language and speech. 23 Because brain stimulation techniques are less effective for WM tracts than for GM, evaluating the morphologic localization of the AF is essential for appropriate presurgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…18,22) The present findings further suggest the diagnostic applicability of DTI for aphasia. 30,[34][35][36] Previous DTI studies in normal subjects reported that fiber connection is greater in the left arcuate fasciculus than in the right, 5,37) implying left brain dominance for language function in humans. To reevaluate this issue, we set ROIs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…23) Previous DTI studies of aphasia caused by stroke reported that FA decreased in the left arcuate fasciculus and adjacent white matter fibers. 5,[27][28][29][30][31][32] In accordance with these previous findings, we set ROIs to include the arcuate fasciculus as defined in the skeletonized FA images (shown in Fig. 1).…”
Section: Image Processingmentioning
confidence: 99%
“…Lower FA values in the superior longitudinal and arcuate fasciculi of the left hemisphere were correlated with decreased ability to repeat spoken language, and lower FA values in the arcuate fasciculus were associated with comprehension deficits; these relationships were independent of the degree of damage to cortical areas [60]. The outcome of aphasia was improved in patients whose left FA could be reconstructed [61]. …”
Section: Structural Imagingmentioning
confidence: 99%